Methyldopa and propranolol or practolol in moderate hypertension. Issue 6028 (17th July 1976) - Petrie, J C; Galloway, D B; Jeffers, T A; Millar, H R; Smith, M C; Wood, R A; Lewis, J A; Simpson, W T
Abstract : The effect of a low dose of methyldopa combined with (a) a non-selective and (b) a selective beta-adrenoceptor antagonist was studied in a double-blind crossover trial in 24 carefully selected patients with moderate hypertension (mean initial lying blood pressure 189/117 mm Hg). Each patient received methyldopa 750 mg/day, propranolol 240 mg/day, practolol 600 mg/day, methyldopa 750 mg/day combined with propranolol 240 mg/day, methyldopa 750 mg/day combined with practolol 600 mg/day, and placebo for four weeks each according to a random sequence. After four weeks of therapy the most effective treatment, methyldopa combined with propranolol, reduced lying and standing blood pressures by 36-5/21-4 mm Hg and 44-7/25 mm Hg respectively. Thic combination had similar effects to those of the combination of methyldopa with the cardioselective agent practolol except that it reduced lying diastolic pressure further. The combination was more effective than either treatment alone. No significant differences were found between the effects of propranolol, practolol, or methyldopa at the doses used.